29th Baltic Conference on the History of Science in Vilnius - Kondratas, Ramūnas; Railienė, Birutė (Vilnius University Proceedings, 2019)
Welcome to the 29th Baltic Conference on the History of Science. This conference carries on the tradition of rotating conferences in the Baltic countries (now including Finland) which was begun in the summer of 1958. This year it is part of Vilnius University’s celebration of its 440th anniversary, and thus the theme Science and the University. The lectures in our plenary session will explore in greater depth the founding during the interwar period of the major national universities in the Baltic States and Finland. The presentations in our general sessions are divided into five sections: medicine, biological sciences, physical sciences, science and technology, and philosophy. In addition to presenters from the Baltic States and Finland, there will be representatives from Poland, Russia, Ukraine and the United States. I would like to thank the members of the organizing and local arrangements committees for their help, and especially Birutė Railienė, the secretary-treasurer of the Lithuanian Association of the History and Philosophy of Science, and Barbara Omelčenko, the Vilnius University Museum administrator. We are very grateful for support from Vilnius University which has provided the facilities for our conference and the very generous financial contribution from Thermo Fisher Scientific Baltics. The organization of this conference in Lithuania began under the very able leadership of Prof. Juozapas Algimantas Krikštopaitis, who was the heart and soul and long-time head of the Lithuanian Association of the History and Philosophy of Science. Unfortunately, he died last year and passed the baton onto me. An In Memoriam for Prof. Krikštopaitis can be found in the front of the abstract booklet. In the name of us all, I would like to dedicate this conference in his memory.Dr. Ramūnas KondratasPresident, Baltic Association of the History and Philosophy of SciencePresident, Lithuanian Association of the History and Philosophy of Science
Keywords: none